Theory of social involvement : a case study in the anthropology of religion, state, and society - Aigbe, Sunday A., 1957- (University Press of America, 1993)
Theory of Social Involvement examines the dynamic interplay between church, state, and society. Sunday A. Aigbe considers the Christian factor as it relates to the sociopolitical responsibility and development in Nigeria and identifies ways in which Christianity can serve as an agent of change and promote unity within Nigeria.